Image Based Sexual Abuse: The Effectiveness of Malawi s Legal Framework - Kanyongolo, Ulemu (Department of Public Law, 2025)
The prevalence of technology and social media has resulted in gender-based violence going beyond the physical and into the digital space. Violence against women which occurs online or with the use of technological means is referred to as technology-facilitated violence, a term which includes a plethora of actions such as harassment and image based sexual abuse. Image based sexual abuse (IBSA) is “non-consensual sharing of images or videos- real or fake- that are either sexually suggestive or sexually explicit.” Although non-consensual sharing of images is certainly not a new phenomenon, increased use in social media and technology contributes to IBSA becoming more widespread, and women are on the receiving end of the majority of image based sexual abuse. IBSA infringes on the right to privacy because the pictures which are shared are sexual or intimate in nature and they are directed at an unintended audience without consent.5 Rackley and McGlynn argue that such a violation is two-fold. Firstly, it may occur where a perpetrator breaches the trust of a victim and non-consensually distributes images that were consensually created; and secondly, such a violation may occur where the image is both created and disseminated without consent.6 Rackley and McGlynn also argue that in both instances, the right to privacy is not derived from the intimate nature of the image, but from a breach of the victim's trust. The right to privacy is constitutionally protected in Malawi.7 Section 21 of the Constitution states, “Every person shall have the right to personal privacy”. Women's right to privacy is in constant threat with the prevalence of IBSA. Malawi is no exception to this phenomenon, and the question arises whether the Malawian legal framework addresses IBSA. Malawian women whose privacy is violated because of IBSA are usually unable to seek redress because as Chisala-Templehoff argues, many people do not know about Malawi's laws